Practices and drivers for antibiotic use in cattle production systems in Kenya - Kisoo, Lydiah; Muloi, Dishon; Oguta, Walter; Ronoh, Daisy; Kirwa, Lynn; Akoko, James M.; Fèvre, Eric M.; Moodley, Arshnee; Wambua, Lillian (Elsevier, 2023)
Understanding antibiotic use in livestock systems is key in combating antimicrobial resistance (AMR) and developing effective interventions. Using a standardised questionnaire, we investigated the patterns and drivers of antibiotic use in 165 cattle farms across the three major cattle production systems in Kenya: intensive, extensive, and semi-intensive systems across in three counties: Machakos, Makueni and Narok in Kenya. We used a causal diagram to inform regression models to explore the drivers of antibiotic use in the study farms. Antibiotic use was reported in 92.7% of farms, primarily for prophylactic purposes. Oxytetracycline, penicillin, and streptomycin were the most used antibiotics to treat and control the most reported diseases including mastitis, diarrhoea and East Coast fever (ECF). Regression analysis indicated a positive association between the frequency of antibiotic use at the farm level and both disease incidence and herd size. Conversely, farms that provided cattle with appropriate housing were less likely to use antibiotics, and there was no difference in antibiotic use between those who consulted with veterinarians or sourced antibiotics directly from animal health providers. Our study highlights the complexities around understanding the interplay between practices and drivers of antibiotic use. It also underscores the necessity to enhance education regarding the appropriate usage of antibiotics among cattle farmers, encourage the adoption of proper herd management practices which may reduce disease burden, and reinforce veterinary services and supportive legislation to promote the prudent use of antimicrobials.